Soil quality and spatial variability of physico-chemical properties of a fruit growing area in Kluang, Malaysia - Moe, Shwe Sin (2011)
Soil quality is a composite picture of the condition of soil for specific function. The general objective of the study is to assess soil quality status of each study area and spatial distribution of major soil nutrients in fruit growing areas to provide the information for effective nutrient application.In this study, the systematic method for rating soil quality proposed by Karlen and Stott (1994) was used to evaluate the soil quality indices of a fruit growing area located in the Modern Agriculture Farm, Kluang (2.00564477' N and 103.19889165' E with elevation 30.4 m above sea level). The four study sites include a banana area, a jackfruit area, a lime area and a fallow or uncultivated area with a total of about 16.3 ha. The soil samples for soil physico-chemical analyses were taken using a stainless steel auger at a depth of 0-20 cm, 20-40 cm and 40-60 cm respectively. For microbial biomass carbon and nitrogen analyses, soil samples were also taken at a depth of 0-10cm for all the areas. Soil physicochemical properties determined were soil pH, total nitrogen (TN), organic carbon (OC), available phosphorus (AP), cation exchange capacity (CEC) and exchangeable potassium (K), exchangeable calcium (Ca) and exchangeable magnesium (Mg). Latitude and longitude of the study area at each sampling point was taken using a hand held GPS (Trimble Geo XH). At each sampling point, three bulk samples were taken and mixed to get a composite sample.Microbial biomass C and N analyses were carried out using chloroform fumigation extraction method. The descriptive statistics and correlation study were analyzed using SAS 9.2 statistics software and Sigma Plot 11.0 software. Geostatistical analysis was carried out using Gamma design software (GS+ version 5.0) and spatial maps of the study area and major nutrients were registered into Map Info Professional software for GIS manipulation. Significant differences were found in some soil properties. The chemical soil properties of the top soils (pH, OC and CEC) were significantly different between fruit growing areas with uncultivated area. The values of soil nutrients (TN, available P,exchangeable K, Ca and Mg) in three fruit growing areas also showed significant differences with uncultivated area. However, in the case of bulk density and porosity, there is no significant difference between three fruit areas with uncultivated area (p = 0.05). The correlation between the soil chemical properties at top soils in banana area showed negative correlation between pH and OC (r = 0.335, n=60), while positive correlations were found between pH and AP (r = 0.358, n=60),between CEC and OC (r = 0.432, n=60) and between Ca and Mg (r = 0.449,n=60), respectively. In the jackfruit area, significant positive correlations were obtained between TN and CEC (r = 0.45, n=30), and between TN and AP (r =0.352, n=30) while negative correlation was found between OC and Ca (r =0.418, n=30). In the lime area, the significant positive correlations were found between pH and TN (r = 0.356, n=30), OC and TN (r = 0.46), and Ca and AP (r= 0.376, n=30), respectively. The status of soil nutrients of the three fruit growing areas were compared with other Malaysian soils. In banana and jackfruit areas, N, P and K status were low in comparison with other Malaysian soils, whereas in lime area, it is low in N and P and moderate in K status. The application of N, P and K fertilizers should be applied in all fruit growing areas because of the low status of these soil nutrients. Geostatistical analysis of soil pH and soil nutrients of the three fruit growing and an uncultivated area was also carried out. The best fitted semivariogram models of pH, TN, AP and EK were spherical, linear, linear and exponential,respectively, in the banana area; linear, spherical, spherical and linear,respectively, in the jackfruit area; linear, exponential, linear and exponential, respectively, in the lime area, and spherical, linear, exponential and linear, in the uncultivated area. The strong spatial dependency was only found for pH in the banana area. Moderate spatial dependencies were found for EK in banana area, for TN and AP in jackfruit area, for TN and EK in lime area and pH and AP in uncultivated area. Moreover, weak spatial dependencies were found for TN and AP in banana area, for pH and EK in jackfruit area, for pH and AP in lime area and TN and EK in uncultivated area, respectively. The spatial distributions of these soil properties at each area were shown in variation map of each soil properties, and the required amount of fertilizer needed to supply each nutrient for successful cultivation an be calculated based on the ranges of nutrients distributed in each fruit growing area. The evaluation of soil quality indices for the three fruit growing areas (banana, jackfruit and lime) and an uncultivated area showed different soil quality index score for each area. The soil quality index scores for the four areas are as follows: jackfruit > lime > banana > fallow. The score of soil quality for each area was calculated by integrating the essential soil functions such as accommodating water entry, facilitating water movement and availability, resistance to surface structure degradation, and sustainability of fruit quality and productivity. The scores of each soil function were also different with each study area and this can be seen through the effect of different cultural practices on soil function. For the function of accommodating water entry, the function scores showed the order: jackfruit (0.18) > banana (0.17) > lime (0.16) > fallow (0.13). For the function score of facilitating water movement and availability, the order was jackfruit (0.15) >banana (0.14) > lime (0.13) > ncultivated (0.12). However, for the function score of surface structure resistance and degradation, the results showed the order of: jackfruit and uncultivated (0.16) > lime (0.15) > banana (0.13). The function score of sustainability of fruit quality and productivity, the result showed the order: lime (0.83) > jackfruit (0.41) > banana (0.33) > uncultivated (0.32). The grand total soil quality scores of the four study areas are jackfruit area=0.90; lime area=0.89; banana area=0.77; fallow=0.69. This showed that the study areas are in good condition both as a successful fruit production and also for sustainable environment. The information of soil quality for each study plot with different cultural practices is useful for the sustainable production of fruit, and also as an indicator for environmental degradation. The presence of microbial communities in soil is also considered an important indicator of soil quality and the position they are found mostly in the top soil regardless of their availability and management practices are also highly dependent on soil nutrient status. Quality information for each plot of land with the study of different cultural practices is useful for continuous production of fruit and caring environmental impact of decomposition.